PELAKSANAAN FUNGSI BADAN PERMUSYAWARATAN DESA DALAM PEMBENTUKAN PERATURAN DESA DI DESA TANJUNGSARI KECAMATAN GUNUNGTANJUNG KABUPATEN TASIKMALAYA - Anjasmara, Shehabudhi Septian; Achmad, Achmad (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2018)
This article examines how the implementation of the functions of the Village Consultative Body (BPD) of Tanjungsari Village in the formation of village regulations in Tanjungsari Village, Gunungtanjung District, Tasikmalaya Regency. This article is compiled based on descriptive empirical legal research with a qualitative approach, the types and sources of research data used are primary data and secondary data, with data collection techniques through interviews, questionnaires and textual study information retrieval to assess secondary data, then further analyzed. using data analysis techniques with a qualitative analysis model. The results show that the BPD of Tanjungsari Village when carrying out its function in the formation of village regulations has not played its role optimally in one of the stages of forming village regulations, where the role of the Tanjungsari Village BPD is at the discussion stage of the village regulation draft which should discuss and agree on the village regulation draft, BPD Desa Tanjungsari only agreed on the final result and did not participate in discussing it, then the BPD of Tanjungsari Village also did not do much in terms of channeling the aspirations of the community towards the Tanjungsari Village Government which led to a mutual agreement between the Tanjungsari Village Government and the BPD of Tanjungsari Village in forming village regulations to be inconsistent with aspirations the people. This happens because there are still several factors that hinder the implementation of the functions of the BPD of Tanjungsari Village in the formation of village regulations including, first communication, second inadequate resources, the third disposition, in this case the attitude or character of the Tanjungsari Village BPD leadership and the four bureaucratic structures that have not yet been implemented well.